A Study on Vibrations of Hexarot-Based High-G Centrifugal Simulators. Issue 2 (21st May 2019) - Pedrammehr, Siamak; Asadi, Houshyar; Nahavandi, Saeid
Summary: This paper investigates the vibrations of hexarot simulators. The generalized modeling of kinematics and dynamics formulation of a hexarot mechanism is addressed. This model considers the flexible manipulator with the base motion. The dynamic formulation has been developed based on the principle of virtual work. The dynamic model consists of the stiffness of the different parts of the mechanism, the effects of gravity and inertia, torque and force related to the joints viscous friction. Finally, the response of the end effector at various frequencies has been presented, and the vibrations of the mechanism and the dynamic stability index have been investigated.